How The Information Of Digital Bank Performance Affects The Firm Value Of Their Affiliated Parent Companies In Asia - Ester Griselia; Dony Abdul Chalid (UNIVED Press, 2026)
This study aims to examine whether the information of digital banks performance adds value or negatively impacts the value of their parent companies in Asia, and to determine whether this impact differs depending on the sector of the parent company. The population of this study consists of digital banks and their parent companies in Asia during the 2021–2023 period. Using purposive sampling, a sample of 19 digital banks and their parent companies was selected. The findings reveal that the information of digital banks performance negatively impacts the value of their parent companies. An increase in ROE in digital banks reduces Tobin’s Q and stock returns of the parent companies due to high perceived risks and the substantial investment required to support the growth of digital banks. High NPL and LDR negatively affect the firm value of the parent companies, reflecting investor concerns regarding risk management and the efficiency of digital banks. In addition, parent companies in the financial sector tend to experience a more positive impact on stock returns compared to those in the non-financial sector. Therefore, based on the research findings, parent companies should adopt a more cautious and strategic approach when investing in digital banks. While digital banks offer growth potential, their high initial operational costs, credit risk (NPL), and pressure on financial ratios such as LDR can negatively affect the value of their parent companies.